Morphology and mechanical properties of PET/PE blends compatibilized by nanoclays: Effect of thermal stability of nanofiller organic modifier. Issue 5 (28th August 2012) - Yousfi, M.; Soulestin, J.; Vergnes, B.; Lacrampe, M. F.; Krawczak, P.
Abstract Poly(ethylene terephtalate)/poly(ethylene) (PET/PE) blends (80/20 wt %) were prepared by melt‐extrusion and compatibilized by addition of nanoclays. Two commercially available organically modified montmorillonites (Cloisite© 10A and 30B) were chosen as reference and a third one was specially organomodified at lab scale with a thermally stable phosphonium surfactant using conventional cationic exchange reaction. The size of the dispersed polymer phase (PE droplets) and the ductility of the blends depend more on the thermal stability of the surfactant of the organomodified clay than on the enthalpic interactions between the blend components and the surfactants used for the modification of the clays. The highest mechanical properties (yield stress and elongation at break) and the better compatibilization efficiency (smallest dispersed PE droplets) were observed in the presence of phosphonium organomodified montmorillonite compared to other less thermally stable commercial organoclays. The analysis of the thermal stability, morphology, and mechanical properties of PET/PE blends containing the surfactants alone in the absence of clay made it possible to evidence separately the effects of the surfactant and of the nanofiller. The role of the surfactant as compatibilization agent was demonstrated. In the absence of nanofiller, the finest morphological and highest ductility were again obtained with the phosphonium surfactant which is the most thermally stable. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013